The association between dietary intake of flavonoids and its subclasses and the risk of metabolic syndrome - Zhao, Zhenlei; Gao, Wenyan; Ding, Xiaoli; Xu, Xiaogang; Xiao, Changqian; Mao, Genxiang; Xing, Wenmin (Frontiers in Nutrition, 2023)
Background: The healthiest way to prevent metabolic syndrome (MetS) is through behavioral and nutritional adjustments. We examined the relationship between total flavonoids intake, flavonoid subclasses, and clinically manifest MetS. Methods: A cross-sectional analysis was conducted among 28,719 individuals from National Health and Nutrition Examination Survey (NHANES) and Food and Nutrient Database for Dietary Studies (FNDDS) 2007-2011 and 2017-2018. Two 24-h reviews were conducted to determine flavonoids intake and subclasses. The link between flavonoids intake and MetS was investigated using a multivariate logistic regression model. Results: Q2 and Q3 of total flavonoids intake were associated with 20% and 19% lower risk of incident MetS after adjusting age and sex. Anthocyanidins and flavanones intake in Q2 and Q3 substantially reduced the MetS risk compared to Q1. MetS risk decreased steadily as the total intake of flavonoids increased to 237.67 mg/d. Flavanones and anthocyanidins also displayed V-shaped relationship curves (34.37 and 23.13 mg/d). Conclusion: MetS was adversely linked with total flavonoids intake, flavanones, and anthocyanidins. Moreover, the most effective doses of total flavonoids, flavanones, and anthocyanidins were 237.67, 34.37, and 23.13 mg/d, respectively, potentially preventing MetS.